Mapping of tropical marine benthic habitat: Hydroacoustic classification of coral reefs environment using single-beam (RoxAnn™) system - Lee, Wah Sze; Lin, Chin Yik (Elsevier, 2018)
Field studies on the performance and discussion of RoxAnn™ Acoustic Ground Discrimination System (AGDS) in discriminating different coral growth forms are often fractional and limited in tropical waters. The purpose of this study is to bridge the information gaps by conducting field surveys at the surrounding benthic habitats of the largest bay in Borneo – Darvel Bay, Malaysia. Accuracy assessment was carried out to evaluate the integrity of the reef habitat map of a tropical island (Baik Island), using test plot and point sampling method. Despite the unsatisfactory test plot method, we found that point sampling method yielded a better internal accuracy of 78%. We demonstrated that factors such as orientation to shore and water depth do not impose significant influence to the AGDS performance using U-Mann-Whitney tests and regression analysis. Overall, the resulting island's habitat map exhibits decent repeatability with map accuracy higher than 80%. The penultimate section of this manuscript also evaluates and provides beneficial information on the potential and strength of AGDS system and its inherent limitation in classifying benthic substrate to a preferred level of details based on the user requirement.